2021
DOI: 10.21203/rs.3.rs-438168/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID 19 disease independently predicted endothelial dysfunction measured by flow-mediated dilatation

Abstract: Background: The systemic effects of COVID-19 disease are still largely uncertain and needs to be scrutinized with further trials. Endothelial dysfunction (ED) is responsible of the majority of adverse cardiovascular events. Flow-mediated dilation (FMD) is easily obtainable method to assess ED accurately. It is aimed to evaluate ED by measuring FMD following COVID-19 disease.Methods: Patients diagnosed with COVID-19 disease were recruited to the hospital two month after the discharge. Sex and age-matched health… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Recent studies have reported endothelial dysfunction in patients with COVID-19 and convalescent survivors reflected by reduced brachial artery flow-mediated dilation (FMD) in response to hyperemia, which is a non-invasive method to assess systemic vascular endothelial function (11)(12)(13)(14)(15). However, these studies have been limited by their short interval between diagnosis and follow-up ranging from 23 to 120 days.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported endothelial dysfunction in patients with COVID-19 and convalescent survivors reflected by reduced brachial artery flow-mediated dilation (FMD) in response to hyperemia, which is a non-invasive method to assess systemic vascular endothelial function (11)(12)(13)(14)(15). However, these studies have been limited by their short interval between diagnosis and follow-up ranging from 23 to 120 days.…”
Section: Introductionmentioning
confidence: 99%